Understanding support for democracy in new and old democracies in the Americas: the role of democratic experience. Issue 6 (18th August 2019) - Camacho, Luis A.
ABSTRACT: This article develops and evaluates a set of expectations regarding the mechanisms via which democratic experience could shape support for democracy. In line with previous studies, one straightforward possibility considered is that experience with democracy fosters greater affective support for democracy, making citizens of old democracies more supportive of this regime independently of government performance and other characteristics. Another possibility considered is that democratic experience mediates the importance of performance assessments in citizens' judgments about democracy, decreasing the importance of economic performance assessments, while increasing that of political performance assessments. Statistical analyses of public opinion data from 23 countries in the Americas indicate that the effect of democratic experience on support for democracy is not statistically significant. Rather, democratic experience conditions the effects of performance assessments on support for democracy. The evidence also supports the assertion that experience with democracy, and not economic development, is what conditions the effects of performance assessments on support for democracy.